Environmental responsibility performance and sales growth: Are service companies better? - Trisninik Ratih Wulandari; Bimo Saktiawan; Tastaftiyan Risfandy (Jurnal Manajemen dan Pemasaran Jasa, 2025)
Concern about the environment continues to intensify amid the issues of global warming and climate change. Encourages consumers and the public to demand that companies do more to improve their environmental responsibility performance. As a developing country, Indonesia's environmental performance could be more effective than that of developed countries. This research investigates whether environmental responsibility performance affects sales growth. Using Refinitiv data on environmental responsibility performance and company financial report data in Indonesia from 2016-2022. The results showed that increasing environmental responsibility performance will have a positive and significant impact on the company's sales growth. Enhancing environmental responsibility performance will foster a positive image among consumers and society. The company's steps in improving environmental responsibility performance are reducing costs and creating environmentally friendly products. This product will attract more consumers and increase sales growth. However, after comparing service and non-service companies, we found that environmental performance is only significant in non-service companies. Because non-service companies' products and consumer expectations are directly related to environmental responsibility performance, they receive the benefits. On the one hand, the government can contribute to increasing environmental responsibility performance by issuing regulations and providing incentives or subsidies, especially for service companies.